(untitled) (Research, Society and Development, 2021)
Platelet-rich fibrin (PRF) is considered a filler biomaterial, currently used in both the medical and dental fields. This work aims to evaluate the use of PRF in aesthetic procedures and whether its use has rejuvenating action on the face. The study uses the terms "Platelet-rich fibrin", "Facial rejuvenation", "Tissue engineering" and "Cosmetic dentistry" to refine the search in the databases: PUBMED, MEDLINE and LILACS, between the beginning of the year 2016 to March of 2021. The criteria for inclusion of the articles were the use of the PRF in case studies and clinical trials in face rejuvenation. The exclusion criteria eliminated repeated studies that adopted a different design from the one mentioned above, or that addressed a therapy using the PRF that was not on the face. The search revealed experimental or observational studies considered eligible, which were included in the qualitative synthesis. The studies included showed that there is no standardization regarding the preparation of the PRF, with different application protocols for this biomaterial, and that although the authors were successful and observed improvement in relation to the appearance of the skin, there is a "high" or "undefined" risk bias favoring positive results. It was concluded that PRF is a safe material and has improved the appearance of the skin, requiring further studies to analyze its long-term effect.